Being an Armenian in Anatolia: narratives of loss and recuperation - Özden, Can. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2014., 2014)
This thesis, which is based on an oral history research with Armenians who have migrated from Anatolia to Istanbul in the last few decades, investigates the formation of Armenian identity in the present. As there are no official records about Armenians living in Anatolia and those who had converted to Islam after the genocide and as recent studies are very limited in number, the most important document becomes oral history narratives. Analyzing Armenians’ lived experiences, memories and postmemories in narratives, this thesis argues that the Armenian identity is associated with resistance against the state and societal norms. Yet this resistance takes multiple meanings and forms. It is indeed subjects’ gender, social class and local identity that largely determine how they tell their stories of resistance and against whom they should resist. Conversion, marriage and migration emerge as main strategies of Armenians in Anatolia to survive and protect their identity. Furthermore, this thesis shows that the 1915 stands as the origin of familial histories and personal life stories as due to the genocide many Armenians today cannot trace their genealogy in the pre-1915 era and as they start telling their life stories with the 1915. This thesis, therefore, argues that the 1915 is not simply a date that points to a specific time in history but an era in which Armenians still live. Accordingly this thesis looks at how some major events that occurred after the genocide such as confiscation of Armenian properties, the Democrat Party’s election victory, September 6-7, the emergence of ASALA and assassination of Hrant Dink are experienced and narrated by Armenians.
Keywords: Armenians -- Turkey -- History.; Armenian massacres, 1915-1923.